The Role of EUSPA in Innovation and Startup Ecosystem within the Czech Republic - Hrnek, Bohuš; Hnát, Pavel, 1981-; Vlčková, Jana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis analyses the role and influence of the European Union Agency for the Space Programme (EUSPA) within the Czech space innovation ecosystem. The research evaluates how EUSPA contributes to the Czech space innovation ecosystem, and how its presence in Prague translates into practical benefits for national stakeholders. The study applies the MIT Innovation Ecosystem Stakeholder Model and draws on qualitative data from semi-structured interviews with start-ups, SMEs, corporate suppliers, public administration and EUSPA representatives. The findings show that EUSPA is strategically important for Czechia, particularly in the downstream space segment, where grants, procurements, prizes and entrepreneurship mechanisms support technological development and reduce R&D risk. Several Czech companies reported direct benefits from these instruments, including increased research capacity and improved access to European markets. EUSPA also contributes to knowledge dissemination through publications, events and user-oriented platforms. At the same time, the impact of EUSPA remains uneven. Administrative complexity and demanding reporting requirements limit participation, especially for SMEs and early-stage firms. Stakeholders also highlighted weak follow-up after programmes such as CASSINI, limited local engagement despite geographic proximity, and ongoing confusion between EUSPA and ESA agencies. National-level fragmentation and labour-market shortages further restrict the effective integration of EUSPA’s activities into the Czech space innovation environment. Overall, the thesis concludes that EUSPA strengthens Czech downstream innovation capacity but remains only partially embedded in the domestic ecosystem. To maximise benefits, the study recommends reduced administrative barriers, stronger mentoring and continuity, clearer institutional communication, deeper cooperation with Czech innovation actors and expanded outreach to non-space sectors.
Vedoucí práce: Pavel Hnát
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses